THE EFFECT OF BLENDED LEARNING MODEL WITH TELEGRAM APPLICATION ON STUDENTS’ CRITICAL THINKING ABILITY AND LEARNING OUTCOMES ON SOCIAL STUDIES SUBJECT AT ELEMENTARY SCHOOL - Santi Wahyuningtias; Yatim Riyanto; Rr Nanik Setyowati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the effect of blended learning model with telegram application on students’ critical thinking skills and learning outcomes for social studies subjects at fifth grade of SDN Semambung Sidoarjo. The blended learning model with the telegram application was carried out online and offline; this also became a solution due to the covid-19 pandemic so that the learning process could still be carried out. This research was an experimental research with a pretest post test control group design. The subject of this research was the fifth grade students of SDN Semambung Sidoarjo. Data were collected through critical thinking ability test and learning outcomes tests. Furthermore, the data were tested by using validity and reliability tests, while the learning tools were tested by expert validation. Data analysis test was conducted through normality test and homogeneity test. The analytical technique used was t test. The results of this study indicated that (1) there was an effect of blended learning model with telegram application on the students’ critical thinking skills at fifth grade elementary school in social studies subject; (2) there was an effect of blended learning model with telegram application on the students’ learning outcomes at the fifth grade elementary school in social studies subject. For teachers who faced problems in implementing online learning accompanied by low critical thinking skills and students’ learning outcomes, it was recommended to use a blended learning model with telegram application.